An Experimental Design for Simultaneous Determination of Carbendazim and Fenamiphos by Electrochemical Method. Issue 4 (16th November 2015) - Lima, T.; Silva, H. T. D.; Labuto, G.; Simões, F. R.; Codognoto, L.
Abstract: This study is aimed to develop an electroanalytical methodology using a boron‐doped diamond electrode (BDD) associated with experimental design in order to determine simultaneously and selectively carbendazin (CBZ) and fenamiphos (FNP) pesticides. In previous studies oxidation peaks were observed at 1.10 V (CBZ) and 1.20 V (FNP), respectively, with characteristics of irreversible processes controlled by diffusion of species (in pH 2.0 (CBZ) and pH 3.5 (FNP)) using a BR buffer 0.1 mol L −1 as support electrolyte. The differences between the potentials for both pesticides, (about 100 mV) indicate the possibility of selective determination of FNP and CBZ. However, employing an equimolar mixture of analytes, the peaks overlap to form a single oxidation peak. Thus, we used a 3 4 full factorial design with four parameters to be analyzed in three levels, in order to obtain the optimized parameters for the separation of the peaks. The best separation conditions were pH 5.0, square wave frequency of 300 s −1, pulse amplitude of 10 mV and scan increment of 2 mV. These parameters were used to obtain the calibration curves of CBZ and FNP. For CBZ the analytical curve was obtained in the concentration range of 4.95×10 −6 to 6.90×10 −5  mol L −1 with good sensitivity and linearity (0.175 A/mol L −1 and 0.999, respectively). The limits of detection (LOD) and quantification (LOQ) were 1.6×10 −6  mol L −1 and 5.5×10 −6  mol L −1, respectively. For FNP the linear concentration interval was 4.95×10 −6 to 3.67×10 −5  mol L −1, with a sensitivity of 0, 207 A/mol L −1 and linearity of 0.996. The LOD and LOQ were 4.1×10 −6  mol L −1 and 13.7×10 −6  mol L −1, respectively. Using these experimental conditions it was possible to separate the oxidation peaks of CBZ (Ep =1.08 V) and FNP (Ep =1.23 V). The electroanlytical method was applied in lemon juice samples. The recovery values were 110.0 % and 92.5 % for CBZ and FNP, respectively. The results showed that the developed method is suitable for application in foodstuff samples. Abstract :